The significance of tubular and glomerular proteinuria in critically ill patients with severe acute kidney injury - Lim, Christopher Thiam Seong; Tan, Han Khim; Lau, Yeow Kok (Professional Medical Publications, 2014)
Objective: Critically ill patients with acute kidney injury (AKI) frequently need acute renal replacement therapy (aRRT). We evaluated an inexpensive, rapid quantitative and qualitative analysis of proteinuria on the course of AKI patients requiring aRRT in intensive care.